Citrus Research Horticultural and Human Health Aspects - Pereira Gonzatto, Mateus; Scherer Santos, Júlia (IntechOpen, 2023)
This book highlights advances in citrus production, focusing on horticultural and human health aspects. In contrast to most publications on citrus, this book discusses both citrus production and the effects of citrus on human health. It is organized into three sections on "Citrus Physiology and Production Technology", "Citrus Pests and Disease", and "Citrus in Human Health". Chapters address citrus production, physiology, diseases, and pests, and much more.